Development of a local empirical model of ionospheric total electron content (TEC) and its application for studying solar-ionospheric effects - Pantea Davoudifar (Nature Portfolio, 2021)
Abstract Regular and irregular variations in total electron content (TEC) are one of the most significant observables in ionospheric studies. During the solar cycle 24, the variability of ionosphere is studied using global positioning system derived TEC at a mid-latitude station, Tehran (35.70N, 51.33E). Based on solar radio flux and seasonal and local time-dependent features of TEC values, a semi-empirical model is developed to represent its monthly/hourly mean values. Observed values of TEC and the results of our semi-empirical model then are compared with estimated values of a standard plasmasphere–ionosphere model. The outcome of this model is an expected mean TEC value considering the monthly/hourly regular effects of solar origin. Thus, it is possible to use it for monitoring irregular effects induced by solar events. As a result, the connection of TEC variations with solar activities are studied for the case of coronal mass ejections accompanying extreme solar flares. TEC response to solar flares of class X is well reproduced by this model. Our resulting values show that the most powerful flares (i.e. class X) induce a variation of more than 20 percent in daily TEC extent.